Beaucarnea olsonii (Ruscaceae), a new species of ponytail palm from southwestern Puebla, Mexico - Rojas-Piña, Vanessa; Alvarado-Cárdenas, Leonardo O. (Phytotaxa, 2016)
Beaucarnea olsonii is described and illustrated from tropical deciduous forests of SW Puebla, Mexico. The new species can be distinguished from other Beaucarnea species by its massively swollen base that abruptly tapers into slender branches, by its conspicuously long stigma, and by its pedicel articulation that occurs at 2/3 of the length of the pedicel below the flower. With this new addition, the total number of endemic species of Beaucarnea for Mexico increases to 10, making this country the greatest center of diversification and endemism for the genus. We also provide a distribution map and a conservation status recommendation for the new species, as well as a key to the Beaucarnea species of southern central Mexico.